Karateristik Media Penyiaran TVRI Medan dalam Membangunkesatuan di Sumatera Utara - Manurung, Afwan Syahril; Ritonga, Nur Ainun Ghoisani; Lubis, Muhammad Arif (Lembaga Intelektual Muda Maluku, 2024)
This article uses qualitative research with a content study approach to analyze the characteristics of the TVRI North Sumatra broadcast media and its role in forming and strengthening unity in Medan, North Sumatra. This study aims to explore information about programs, news, and the social impact of content broadcasted by TVRI Medan. The data collection techniques used in this study were content analysis and in-depth interviews with TVRI Medan personnel. Content analysis was used to examine the various types of programs broadcasted, as well as to assess the diversity and quality of information provided. In-depth interviews were conducted to gain deeper insight from TVRI Medan staff and personnel regarding the program creation process and its impact on viewers. The data analysis technique used was thematic analysis, which focused on identifying the main themes in the broadcast content, and how these themes can influence viewers and play a role in strengthening unity and togetherness in the North Sumatra community. Data obtained from content analysis and interviews were analyzed to find the relationship between broadcast programs, local cultural diversity, and their impact on public perception. The results of the study indicate that TVRI Medan plays a significant role in promoting local culture, as well as acting as a means to strengthen unity in society through the delivery of information and entertainment